Microbial aspect of aspiration pneumonia in patients with altered consciousness admitted in Dhaka Medical College Hospital, Bangladesh - Chowdhury, Md Rashed Alam; Azad, Khan Abul Kalam; Hossain, Mohammad Zaid; Sardar, Md Hafiz; Siddiqui, Mahmudur Rahman; Saad, Sanjeeda; Rahman, Md Mostafizur (Journal of Dhaka Medical College, 2015)
Context: Aspiration Pneumonia is a common complication in patients with altered consciousness, if general supportive care is not taken properly. There is no national study on microbial aspect of aspiration pneumonia in hospitalized patients with altered consciousness. This study was done to see the microbial aspect of aspiration pneumonia in patients with altered consciousness admitted in a tertiary level hospital in Bangladesh. Methods: A prospective observational study was done on 50 adult patients of aspiration pneumonia with altered consciousness admitted in the medicine department of medicine, Dhaka Medical College Hospital, Dhaka, between January and December 2010. Aspiration pneumonia was confirmed by clinical examination and laboratory investigations. Hematologic measurements, chest x-ray, blood gas analysis, estimation of blood urea, serum creatinine and random blood sugar were done in all patients. Sputum for gram staining and culture & sensitivity as well as blood culture & sensitivity were done in patients who were diagnosed as aspiration pneumonia clinically and radiologically. Validated sputum was cultured in blood agar, chocolate agar and McConkeys agar media. Blood culture was done in trypticase soya broth, blood agar, chocolate agar and McConkeys agar media. Results: The mean age was 38.9±17.3 years. 35 (70%) patients were male and 15 (30%) patients were female. Blood culture was found positive in 30.8% patients who developed aspiration pneumonia among the study patients. In sputum for Gram staining, only Gram positive Cocci was present in 46.15%, only Gram negative Bacilli was present in 38.46%, mixed Gram positive cocci and Gram negative bacilli was present in 7.7% and Gram negative Coccobacilli was found in 7.7% patients who developed aspiration pneumonia among the study patients. In growth positive cases (n=11) sputum culture revealed 45.45% streptococcus pneumoniae, 36.36% Klebsiella pneumoniae, 9% Pseudomonas species and 9% Haemophylus influenzae. The mean duration of hospital stay was 8.12±2.42 days with ranging from 4 to 14 days DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21517 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 110-114